2006
DOI: 10.1080/02652040601034013
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing effects of calcium alginate microspheres on mycobacterium bovis BCG intended for oral vaccination

Abstract: In this study, alginate microspheres containing BCG were prepared at a diameter of approximately 10 microm by emulsification-internal gelation of an alginate-BCG solution dispersed in olive oil using a high rate speed stirrer. The stability of BCG was assayed at 4 degrees C showing that the encapsulated BCG was more stable than free BCG at least for 5 weeks; however, BCG in sodium alginate solution was not stable at all. On the other hand, the studies using media with different pH (1.2, 4.4, 6.2, 6.8 and 7.5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, there are several challenges to successful oral immunization due to the degradation of the antigens in the harsh environment of the gastrointestinal tract. Encapsulation of antigen protects it from enzymatic and chemical destruction of gastric secretions and thus can reduce the prescribed doses . Alginates as biodegradable and biocompatible polymers have been extensively used in biomedical fields such as cell encapsulation and controlled release delivery systems .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are several challenges to successful oral immunization due to the degradation of the antigens in the harsh environment of the gastrointestinal tract. Encapsulation of antigen protects it from enzymatic and chemical destruction of gastric secretions and thus can reduce the prescribed doses . Alginates as biodegradable and biocompatible polymers have been extensively used in biomedical fields such as cell encapsulation and controlled release delivery systems .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that BCG incorporated in alginate microspheres results in increased viability of bacilli in simulated gastric fluid in comparison with free BCG . Furthermore, intragastric administration of BCG encapsulated in alginate microspheres was shown to result in strong systemic protective immune responses against intravenous BCG challenge, 2 months after the immunization .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method of delivery has been investigated for the entrapment and oral delivery of live bacteria as probiotics (Lee and Heo, 2000) or as vaccines (Dobakhti et al, 2006). Although alginates have been shown as promising vehicles for oral delivery there are issues such as drug leaching, imbibing of acid, and competitive inhibition of carboxyl groups by some positively charged proteins affecting stability (Espevik et al, 1993).…”
Section: The Development Of Biopharmaceuticalsmentioning
confidence: 99%
“…In this regard carriers such as chitosan/ alginate, etc have been employed with some degree of success [6,7] . BCG incorporated in alginate microspheres demonstrated an almost ninefold increase in viable bacilli in simulated gastric fluid (SGF) after 1.5 h, in comparison to free BCG, thereby demonstrating the potential of encapsulated BCG for oral vaccination [8] . In another study, alginateencapsulated BCG proved (reduced more colony forming units (CFU)) to be more protective in mice even after oral administration as compared to an un-encapsulated counterpart that was administered either orally or subcutaneously [9] .…”
Section: Tuberculosismentioning
confidence: 99%